PRAWO LEKARSKIE DRUGIEJ RZECZYPOSPOLITEJ W ZARYSIE - Zieliński, Tadeusz J. (Zeszyty Prawnicze, 2016)
LAW REGARDING PHYSICIANS IN THE SECOND REPUBLIC OF POLAND IN OUTLINE Summary Profession of a physician as a key element of the healthcare system was the subject of an intense interest of the legislative power of the Second Republic of Poland (1918-1939). The legal acts analyzed in the present paper expressed the far reaching vision formulated at the outset of the reborn Polish state. That vision is particularly exemplified in the Basic Sanitary Act of 1919 r. The law on physicians of mid-war period underwent gradual and intended evolution. Practical implementation of the Act on the Practice and Chambers of Physicians of 1921 contributed towards an enactment of the highly regarded new regulations of the matter in 1932 and 1934. This was accompanied by the formation of the distinct profession of dentists. Legislative order of the President of the Republic on the healthcare institutions of 1928 played a significant role as far as regulation of the market of medical suppliers is concerned. In the 30s quality of legal acts had been clearly improved. Due to determination of the healthcare authorities after more then a decade of the Second Republic’s legislative activity, there were only few remnants of old occupants’ legal regulations in the area of law on physicians. This remarkable achievement was quite suddenly dismantled, since the repeal of majority of the said acts by the Communist authorities after 1945.